Enhancing Regional Cooperation for Human Security: Insights from ASEANAPOL's 2023 Committee A - Raihanah Dinda Alyfia Rahman (Department of International Relations, Brawijaya University, 2024)
Integration of human security concepts in the 41st ASEANAPOL Meeting, Committee A focusing on enhancing regional cooperation to address complex global security threats. With analyzes how initiatives within ASEANAPOL aim to protect individuals' well-being from various transnational threats, encompassing aspects like personal protection, health, environment, economic, and community security. By using the theory of liberal institutionalism in viewing the existence of ASEANAPOL, and integrating the results of the Commission A meeting at the 41st ASEANAPOL with the concept of human security. The findings underscore the significance of regional institutional cooperation, particularly through ASEANAPOL, in bolstering human security for citizens of member countries and combating transnational crimes effectively. Through discussions on transnational crimes like drugs trafficking, terrorism, arms smuggling, trafficking in persons, and wildlife crimes, the outcomes of the 41st ASEANAPOL Meeting, which include the establishment of specialized task forces and enhanced information sharing, the study underscores the commitment of member countries to enhance collaboration enforcement capacities. the journal emphasizes the importance of human security from diverse transnational threats in the Southeast Asian region.